Adipokines: Novel Players in Resistant Hypertension. Issue 10 (4th September 2014) - de Faria, Ana Paula; Modolo, Rodrigo; Fontana, Vanessa; Moreno, Heitor
<x xml:space="preserve">Abstract</x> Resistant hypertension (RH) is a multifactorial disease, frequently associated with obesity and characterized by blood pressure above goal (140/90 mm Hg) despite the concurrent use of ≥3 antihypertensive drugs of different classes. The mechanisms of obesity‐related hypertension include, among others, aldosterone excess and inflammatory adipokines, which have demonstrated a significant role in the pathogenesis of metabolic syndrome and RH. This review aims to summarize recent studies on the role of the adipokines leptin, resistin, and adiponectin in the pathophysiology of RH and target‐organ damage associated with this condition. The deregulation of adipokine levels has been associated with clinical characteristics frequently recognized in RH such as diabetes, hyperactivity of sympathetic and renin‐angiotensin‐aldosterone systems, and vascular and renal damage. Strategies to regulate adipokines may be promising for the management of RH and some clinical implications must be considered when managing controlled and uncontrolled patients with RH.